Risk and rates of hospitalisation in young children: A prospective study of a South African birth cohort. - Catherine J Wedderburn; Julia Bondar; Marilyn T Lake; Raymond Nhapi; Whitney Barnett; Mark P Nicol; Liz Goddard; Heather J Zar (Public Library of Science (PLoS), 2024)
Children in sub-Saharan Africa (SSA) are disproportionately affected by morbidity and mortality. There is also a growing vulnerable population of children who are HIV-exposed uninfected (HEU). Understanding reasons and risk factors for early-life child hospitalisation will help optimise interventions to improve health outcomes. We investigated hospitalisations from birth to two years in a South African birth cohort study. Mother-child pairs in the Drakenstein Child Health Study were followed from birth to two years with active surveillance for hospital admission and investigation of aetiology and outcome. Incidence, duration, cause, and factors associated with child hospitalisation were investigated, and compared between HEU and HIV-unexposed uninfected (HUU) children. Of 1136 children (247 HEU; 889 HUU), 314 (28%) children were hospitalised in 430 episodes despite >98% childhood vaccination coverage. The highest hospitalisation rate was from 0-6 months, decreasing thereafter; 20% (84/430) of hospitalisations occurred in neonates at birth. Amongst hospitalisations subsequent to discharge after birth, 83% (288/346) had an infectious cause; lower respiratory tract infection (LRTI) was the most common cause (49%;169/346) with respiratory syncytial virus (RSV) responsible for 31% of LRTIs; from 0-6 months, RSV-LRTI accounted for 22% (36/164) of all-cause hospitalisations. HIV exposure was associated with increased incidence rates of hospitalisation in infants (IRR 1.63 [95% CI 1.29-2.05]) and longer hospital admission (p = 0.004). Prematurity (HR 2.82 [95% CI 2.28-3.49]), delayed infant vaccinations (HR 1.43 [95% CI 1.12-1.82]), or raised maternal HIV viral load in HEU infants were risk factors for hospitalisation; breastfeeding was protective (HR 0.69 [95% CI 0.53-0.90]). In conclusion, children in SSA experience high rates of hospitalisation in early life. Infectious causes, especially RSV-LRTI, underly most hospital admissions. HEU children are at greater risk of hospitalisation in infancy compared to HUU children. Available strategies such as promoting breastfeeding, timely vaccination, and optimising antenatal maternal HIV care should be strengthened. New interventions to prevent RSV may have additional impact in reducing hospitalisation.